PRR7 is a transmembrane adaptor protein expressed in activated T cells involved in regulation of T cell receptor signaling and apoptosis - Hrdinka, Matous; Dráber, Peter; Stepánek, Ondrej; Ormsby, Tereza; Otáhal, Pavel; Angelisová, Pavla; Brdicka, Tomás; Paces, Jan; Horejsí, Václav; Drbal, Karel (The Journal of biological chemistry, 2011)
Transmembrane adaptor proteins (TRAPs) are important organizers and regulators of immunoreceptor-mediated signaling. A bioinformatic search revealed several potential novel TRAPs, including a highly conserved protein, proline rich 7 (PRR7), previously described as a component of the PSD-95/N-methyl-d-aspartate receptor protein complex in postsynaptic densities (PSD) of rat neurons. Our data demonstrate that PRR7 is weakly expressed in other tissues but is readily up-regulated in activated human peripheral blood lymphocytes. Transient overexpression of PRR7 in Jurkat T cell line led to gradual apoptotic death dependent on the WW domain binding motif surrounding Tyr-166 in the intracellular part of PRR7. To circumvent the pro-apoptotic effect of PRR7, we generated Jurkat clones with inducible expression of PRR7 (J-iPRR7). In these cells acute induction of PRR7 expression had a dual effect. It resulted in up-regulation of the transcription factor c-Jun and the activation marker CD69 as well as enhanced production of IL-2 after phorbol 12-myristate 13-acetate (PMA) and ionomycin treatment. On the other hand, expression of PRR7 inhibited general tyrosine phosphorylation and calcium influx after T cell receptor cross-linking by antibodies. Moreover, we found PRR7 constitutively tyrosine-phosphorylated and associated with Src. Collectively, these data indicate that PRR7 is a potential regulator of signaling and apoptosis in activated T cells.
Keywords: apoptóza; Ionomycin; Antigens, CD; lidé; interleukin-2; Caco-2 Cells; Antigens, Differentiation, T-Lymphocyte; Gene Expression Regulation; ionomycin; diferenciační antigeny T-lymfocytů; Apoptosis; Amino Acid Motifs; Caco-2 buňky; krysa rodu Rattus; adaptorové proteiny signální transdukční; vápníková signalizace; Phosphorylation; receptory antigenů T-buněk; Humans; U937 Cells; Ionophores; fosforylace; Jurkat buňky; Carcinogens; Tetradecanoylphorbol Acetate; lektiny typu C; T-lymfocyty; Proto-Oncogene Proteins c-jun; ionofory; T-Lymphocytes; Protein Structure, Tertiary; HEK293 Cells; HEK293 buňky; Lectins, C-Type; zvířata; tetradekanoylforbolacetát; Jurkat Cells; Receptors, Antigen, T-Cell; Interleukin-2; Rats; U937 buňky; aminokyselinové motivy; Animals; Calcium Signaling; karcinogeny; regulace genové exprese; Adaptor Proteins, Signal Transducing; CD antigeny; protoonkogenní proteiny c-jun; terciární struktura proteinů